Role of Minimally Invasive Techniques in Combined Urological and General Surgical Procedures - Rehman, Mati Ur; rehman, ishtiaq ur; Farhan Khan, Muhammad; Khan, Bilal Saeed; Khan, Abdullah; khan, Saifullah (Journal of Neonatal Surgery, 2025)
Background Minimally invasive techniques (MIT) in combined urological and general surgical procedures have gained widespread acceptance due to their benefits in reducing patient trauma, enhancing precision, and minimizing recovery time. These techniques, particularly laparoscopic and robotic-assisted surgeries, offer significant advantages in managing complex cases involving multiple organ systems, ensuring faster recovery and improved outcomes. Objectives This study aims to assess the effectiveness of minimally invasive techniques in combined urological and general surgical procedures, focusing on recovery time, complication rates, and patient satisfaction compared to traditional open surgeries. Methodology A prospective cohort study was conducted at department of urology Pak international medical college Peshawar from June 2024 to June 2025. patients undergoing combined urological and general surgical procedures using minimally invasive techniques. Participants were assessed for postoperative recovery, complication rates, and hospital stay duration. Statistical analysis was performed using t-tests, chi-square tests, and regression models to compare outcomes between minimally invasive and traditional open surgical groups. Data was collected preoperatively and postoperatively, with a focus on patient recovery metrics and surgical success. Results The mean age of patients was 58 years, with a standard deviation of 12.5 years. A total of 150 patients were included, with 75 undergoing minimally invasive procedures and 75 receiving traditional open surgery. The postoperative complication rate was significantly lower in the minimally invasive group (p < 0.05). Recovery times were also notably shorter in the minimally invasive group, with a mean recovery time of 6.5 days compared to 12 days in the open surgery group. The p-value for the difference in recovery time was 0.02, indicating a statistically significant advantage for minimally invasive surgery. Conclusion Minimally invasive techniques in combined urological and general surgical procedures significantly improve patient outcomes by reducing recovery time and complication rates. This study supports the growing adoption of MIT for complex surgeries, demonstrating their advantages over traditional open techniques. The results underline the need for further exploration of these approaches in multi-disciplinary surgical settings to refine techniques and optimize patient care...